Linguistic Discoveries: Tracing Grammatical Errors in the Translation of Qasas Al-Nabiyyīn by Abu Hasan Ali Hasani Nadwi - Satori, Achmad; Suparno, Darsita; Aqil Assyauqi, Wahyu; Wahidah, Wardah; Anas, Muhammad; Rokhim, Minatur; Zakaizak, Fathalla Muhamed Fathalla (UIN Sunan Gunung Djati Bandung, 2023)
This article aims to understand the grammatical errors in the translated text of